The Role of Job Satisfaction In Mediating the Effect of Rewards and Career Management On Employee Performance in Plantation Pension Fund Management Institutions - Fadli Priyono; Seta Ariawuri Wicaksana; Nana Nawasiah (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the effect of rewards and career management on employee performance with job satisfaction as a mediating variable at the Plantation Pension Fund (Dana Pensiun Perkebunan). The research is motivated by fluctuations in employee performance achievements and corporate KPI results over recent years, indicating the need for an evaluation of human resource management practices, particularly reward systems and career management. This study employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to all employees of the Plantation Pension Fund. The data were analyzed using SmarPls to examine both direct and indirect relationships among variables.The results indicate that rewards and career management have a positive and significant effect on job satisfaction. Furthermore, rewards and career management also have a positive and significant effect on employee performance. Job satisfaction is proven to have a positive and significant effect on employee performance. The mediation analysis reveals that job satisfaction significantly mediates the relationship between rewards and employee performance, as well as between career management and employee performance. These findings suggest that improving employee performance is not only influenced directly by rewards and career management, but also indirectly through enhanced job satisfaction